Guiding Doctoral Students in the Appropriate and Ethical Use of Artificial Intelligence for the Doctor of Nursing Practice Proposal Development - Lynne Palma; Andre Williams (Journal of Doctoral Nursing Practice, 2026)
Background: Developing a Doctor of Nursing Practice (DNP) project proposal is challenging as students balance clinical skill development and certification preparation. Many proposals lack coherence, alignment, or measurable value. Generative artificial intelligence (AI) tools, such as ChatGPT, present both opportunities and risks in addressing these barriers. Objective: This article advocates for the responsible use of AI to support DNP students in proposal development and implementation while maintaining scholarly rigor and professional standards. Methods: A narrative review of literature on AI in health care and higher education, with emphasis on large language models, was conducted to examine opportunities, threats, and strategies for ethical academic use. Results: AI can enhance idea generation, alignment, and organization of DNP proposals, but risks such as inaccuracy, bias, privacy, and plagiarism remain. Prompt engineering and faculty oversight are essential for appropriate use. Mitigation strategies are presented. Conclusion: AI should augment, not replace, critical thinking and scholarly inquiry. Implications for Nursing: Nurse educators must lead efforts to integrate AI ethically into curricula, fostering innovation while preserving academic integrity and nursing’s humanistic values.